DEVICE FOR CONTROL OF RAW SILK THICKNESS BASED ON OPTOELECTRONIC GENERATOR - Mamasadikov Yusupjan,; Kipchakova Gavkharoy Muhammadsharifovna, (International Journal of Innovations in Engineering Research and Technology, 2023)
The quality of products in the silk industry largely depends on the technological parameters of unwinding silkworm cocoons [1].